2023
DOI: 10.1097/corr.0000000000002506
|View full text |Cite
|
Sign up to set email alerts
|

CORR Synthesis: How Have Film Review and Motion Analysis Been Used to Enhance Orthopaedic Surgical Performance?

Abstract: Each author certifies that there are no funding or commercial associations (consultancies, stock ownership, equity interest, patent/licensing arrangements, etc.) that might pose a conflict of interest in connection with the submitted article related to the author or any immediate family members. All ICMJE Conflict of Interest Forms for authors and Clinical Orthopaedics and Related Research® editors and board members are on file with the publication and can be viewed on request. The opinions expressed are those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Other authors also suggested ways to improve operative efficiency and reduce OR time, such as having an assistant attending surgeon, 32,33 incentivizing the OR team to reduce OR/turnover time 34 and increasing surgical efficiency by video feedback training for surgeons. 35 Similarly, LOS was shown to be higher in the staged group, a finding supported by all the studies included in the analysis. 5,[20][21][22]24,27 This could be explained by the fact that patients had to stay in the hospital between the two staged surgeries, thus increasing LOS.…”
Section: Discussionmentioning
confidence: 53%
“…Other authors also suggested ways to improve operative efficiency and reduce OR time, such as having an assistant attending surgeon, 32,33 incentivizing the OR team to reduce OR/turnover time 34 and increasing surgical efficiency by video feedback training for surgeons. 35 Similarly, LOS was shown to be higher in the staged group, a finding supported by all the studies included in the analysis. 5,[20][21][22]24,27 This could be explained by the fact that patients had to stay in the hospital between the two staged surgeries, thus increasing LOS.…”
Section: Discussionmentioning
confidence: 53%
“…43 In addition, increasing surgical efficiency may be enhanced by video feedback training for surgeons. 44 Despite its logical message that optimizing OR time is beneficial, this study has several potential limitations. The patient population was not matched with regards to BMI, CCI, or all aspects of deformity complexity such as axial or coronal place deformity.…”
Section: Discussionmentioning
confidence: 95%
“…Strategies to improve surgical ergonomics included the use of robotic assistance in TKA and THA, surgical loupes in spine surgery, and automated impaction devices in THA. Although a limited number of studies proposed interventions to improve orthopaedic surgical ergonomics, several targeted interventions were successful in other fields [18,20,37]. To improve orthopaedic surgical ergonomics and mitigate work-related musculoskeletal disorders, we recommend ergonomics and work-injury lectures be offered by hospitals and residency training curricula, and film-based review of surgical techniques to assesses ergonomics in addition to surgical skill.…”
Section: Discussionmentioning
confidence: 99%
“…Because randomized controlled trials with longitudinal ergonomic and work injury monitoring are impractical, the success of ergonomic lectures and workshops ought to be defined by an increase in knowledge and awareness of one's own habits while operating, and the perceived benefit by the surgeon. The emerging adoption and projected growth of film review by hospitals to facilitate the surgical training of residents and practicing surgeons can further increase ergonomic awareness [18]. We propose that film review be used to evaluate not only surgical skills, but also surgical ergonomics, either informally or through the use of validated observational tools [1,2,32,51].…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation